Anthropomorphisms and names of God in The Gospel of Philip (Argos, 2024)
The Gospel of Philip –the third place in the Codex II of the Library of Nag Hammadi– is composed of six other treatises arranged in chronological order as follows: The Apocryphon (secret book) of John (long version); The Gospel of Thomas; The Hypostasis of the Archons; On the Origin of the World (first copy); The Exegesis on the Soul and The Book of Thomas, the Contender. The Gospel of Philip is the most "sacramental" of the Gnostic gospels, since the five main rites: baptism, anointing, the Eucharist, redemption and the bridal chamber are directly mentioned as constituents of a single mystery. Those descriptions are preceded by anthropomorphisms of God, such as "dyer" and "man-eater", as well as by names assigned to divine realities which embrace an esoteric sense inherent to the Valentinian school.
Keywords: Gospel; Sapiential; Valentinian; God; Name